Fragments Shored Against the Ruins: Notes Towards a Definition of European Semiosphere - Brlek, Tomislav (2004)
The assertion proposed by Derrida that it is in the nature of "a culture that it is not identical with itself, " seems to be especially pertinent in the case of European culture, since it has been defined in terms of a unity in diversity already in its initial conceptual elaboration in the work of Francois Guizot. The paper offers to explore this insight through a reading of T.S. Eliot's talk The Unity of European Culture and his poem The Waste Land - both of which address, in their respective modes, the conditions of possibility for Europe as a semiosphere in a situation when its cities are in ruins while a reconcilliation of its fragmented culture seems all but inconceivable - in the light of Benjamin's notion of the ruin as the site where "history has become physically merged with the setting" and "does not assume the form of the process of an eternal life so much as that of irresistible decay."